Intertemporal income shifting around a large tax cut: The case of depreciations - Laura Dobbins; Sebastian Eichfelder; Frank Hechtner; Jochen Hundsdoerfer (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
A corporate tax rate cut provides an incentive for corporations to shift taxable income from years before the tax rate cut to post-reform years. Our study analyzes whether depreciations and write-offs are used to achieve intertemporal income shifting. Using a panel of German manufacturing firms, we test in a difference-in-differences setting whether firms reacted to the announced 2008 corporate tax rate cut of 10 percentage points by accumulating depreciation expenses in the pre-reform year. Our results suggest that depreciation expenses in 2007 are on average about 2.5% higher than in the other observation years. Our analysis also sheds light on heterogeneity in intertemporal income shifting across firms. We provide evidence for a weaker reaction of loss firms resulting from a lower tax incentive. By contrast, we find stronger intertemporal income shifting of large firms and especially firms with a relatively high share of new investments in the capital stock. While the first result is consistent with a higher cost-efficiency of tax planning of large firms, the second finding suggests that investments in the current year provide more discretion for (tax-induced) earnings management.
Keywords: H25; M41; 330; Tax planning; Intertemporal income shifting; Tax avoidance opportunity; Depreciations; Write-offs